EVALUATION OF THE DYNAMICS OF OCCLUSION RATIO DURING ORTHODONTIC TREATMENT OF PATIENTS WITH PERMANENT BITE. - K.M. Lykhota (Український стоматологічний альманах)
The unity of the tooth-jaw system is ensured by the close interaction of dental rows, jaws, chewing and facial muscles, temporomandibular joint. Surgical anomalies of bite are often accompanied by significant changes in occlusion ratio of the tooth-jaw system, which significantly affects the quality of life of patients [1, 2, 3]. Significant influence on occlusion ratio has orthodontic treatment. Introduction of high technologies into the practice of prevention and treatment of abnormalities of the zygomatic system contributes to the improvement of dental health, however, the problem of violation of occlusive ratio in dental anomalies and deformations persists in connection with the increase in the prevalence of bite pathology among the population of Ukraine [4, 5].